2021
DOI: 10.1155/2021/1268352
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fracture Width Change under Closure Pressure in Unconventional Reservoir Based on the Hertz Contact Theory

Abstract: To describe the fracture width is crucial for the flow conductivity evaluation, which influences the exploitation efficiency of unconventional oil and gas resources. Commonly, as the proppants fill in the fracture, the deformation will happen under the closure pressure to resist the fracture width change. Therefore, it is significant to develop the theoretical model to predict the variation. In this work, the mathematical model for the propping behavior of proppants in the fracture under closure pressure is es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The study found that high stress causes increased pore blockage, and larger pores are less likely to experience particle plugging. Closure pressure reduction increases fracture width, as it decreases the contact force between fractured surfaces [30,31]. Chen et al used the Brazilian splitting method to create rough fractures and quantified the effect of proppant concentration on the stress sensitivity of artificial fractures by changing gas flow pressure and confining pressure, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that high stress causes increased pore blockage, and larger pores are less likely to experience particle plugging. Closure pressure reduction increases fracture width, as it decreases the contact force between fractured surfaces [30,31]. Chen et al used the Brazilian splitting method to create rough fractures and quantified the effect of proppant concentration on the stress sensitivity of artificial fractures by changing gas flow pressure and confining pressure, respectively.…”
Section: Introductionmentioning
confidence: 99%